2013
DOI: 10.1097/mib.0b013e318281f506
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte–Macrophage Colony-Stimulating Factor Autoantibodies

Abstract: Background & Aims Neutralizing auto-antibodies (Ab) against granulocyte-macrophage colony-stimulating factor (GM-CSF Ab) have been associated with stricturing ileal Crohn’s disease (CD) in a largely pediatric patient cohort (total 394, adult CD 57). The aim of this study was to examine this association in two independent predominantly adult inflammatory bowel disease patient cohorts. Methods Serum samples from 745 subjects from the NIDDK IBD Genetics Consortium and 737 patients from Australia were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 43 publications
5
38
0
Order By: Relevance
“…A similar observation was published by Gathungu et al, where CD patients with elevated anti-GM-CSF antibody exhibited increased bowel permeability as compared to those with lower levels of this antibody [62]. It has been suggested that GM-CSF neutralization promotes ileac disease by modulating expression of CCL25 by intestinal epithelium and CCR9 by T lymphocytes via Nod2-dependent and -independent pathways [62]. Therefore, increased GM-CSF levels in adult CD may contribute to inhibition of bowel inflammation and prevention of tissue damage.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A similar observation was published by Gathungu et al, where CD patients with elevated anti-GM-CSF antibody exhibited increased bowel permeability as compared to those with lower levels of this antibody [62]. It has been suggested that GM-CSF neutralization promotes ileac disease by modulating expression of CCL25 by intestinal epithelium and CCR9 by T lymphocytes via Nod2-dependent and -independent pathways [62]. Therefore, increased GM-CSF levels in adult CD may contribute to inhibition of bowel inflammation and prevention of tissue damage.…”
Section: Discussionsupporting
confidence: 81%
“…Further, these authors demonstrated that elevated anti-GM-CSF antibody levels were associated with intestinal stricture, penetration, and resection in CD patients. A similar observation was published by Gathungu et al, where CD patients with elevated anti-GM-CSF antibody exhibited increased bowel permeability as compared to those with lower levels of this antibody [62]. It has been suggested that GM-CSF neutralization promotes ileac disease by modulating expression of CCL25 by intestinal epithelium and CCR9 by T lymphocytes via Nod2-dependent and -independent pathways [62].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Disease located in the small bowel [ileal/ileocolonic disease] has been consistently identified as an independent risk factor for surgery in adult populations, 21,38,45,46,47,48 possibly because small bowel disease is more frequently associated with penetrating and stenosing behaviour. 22 Disease located in the jejunum and upper GI tract [L4] is also indicative of higher surgical risk for similar reasons, 11,12,13,14,15,49 while colonic disease [L2] is protective against major surgery. 22,42,49,50,51 …”
Section: Resultsmentioning
confidence: 99%
“…GM-CSF receptor is a heterodimer composed of α and β subunits20. A reduction of macrophages in synovial tissue has been correlated with improvement in the disease activity score, thus antagonizing GM-CSF was found to markedly reduce established disease in mouse models of RA2122. In order to protect the synovial tissue from inflammatory cell infiltration, a synergistic effect will be expected with the combined treatment of paroxetine and GM-CSF inhibitor for RA patients.…”
Section: Discussionmentioning
confidence: 99%